Evaluation of Estradiol and Pro-Inflammatory Marker Level with VAS Score After Progestin Therapy in Endometriosis Patients - Muthalib, Aidrus; Sumapraja, Kanadi; Harzif, Achmad Kemal; Maidarti, Mila (Indonesian Socety of Obstetrics and Gynecology, 2024)
Objectives: To compare estradiol levels and proinflammatory biomarkers (IL-6, IL-1B, and COX-2) in endometriosis patients with pain and without pain after progestin therapy. Methods: This observational cross-sectional study involved 47 endometriosis patients undergoing three months of progestin therapy at RSUPN Cipto Mangunkusumo from March to June 2024. Serum levels of COX-2, IL-6, IL-1B, and estradiol will be measured using ELISA and Microplate Enzyme Immunoassay, with pain status assessed to determine associations between biomarkers and pain presence. Results: A significant difference in COX-2 levels between patients with pain and those without, with higher levels in the pain group [1.845 (1.24-10.26) vs 1.55 (0.32-3.07), p = 0.004]. A significant positive correlation was found between IL-1Beta and IL-6 (r = 0.471, p = 0.001). COX-2 levels also exhibited a weak but statistically significant positive correlation with VAS scores (r = 0.360, p = 0.013). Conclusion: There is a difference in inflammatory markers IL-6, IL-1 Beta and COX-2 in endometriosis patients with progestin therapy who experience pain and painlessness. Keywords: endometriosis, estradiol, proinflammation, progestin therapy.